Collagen matrix vs mitomycin-C in trabeculectomy and combined phacoemulsification and trabeculectomy: a randomized controlled trial. Issue 1 (December 2016) - Tanna, Angelo; Rademaker, Alfred; de Moraes, C.; Godfrey, David; Sarkisian, Steven; Vold, Steven; Ritch, Robert
Abstract Background Antifibrotic agents are commonly utilized to enhance the success rates of trabeculectomy. Novel approaches to further improve success rates and reduce the risks of complications are needed. The purpose of this study was to compare intraocular pressure (IOP)-lowering efficacy and safety of trabeculectomy or combined phacoemulsification and trabeculectomy with mitomycin-C (MMC) vs. Collagen Matrix (CM). Methods A prospective, multicenter, randomized controlled trial was performed. Ninety-five eyes of 94 patients with uncontrolled glaucoma despite medical therapy, without previous incisional glaucoma surgery underwent trabeculectomy (85 eyes) or combined phacoemulsification and trabeculectomy (10 eyes) and were randomized to MMC or CM. One eye of each subject was analyzed. Patients were followed for 24 months. The criteria for complete success were IOP >5 and ≤21 mmHg with at least a 20% reduction below medicated baseline without additional glaucoma surgery or medications. The main outcome measures were complete success rates at 24 months with Kaplan-Meier analysis and incidence of adverse events. Results The baseline IOPs were 20.4 ± 6.0 mmHg and 21.2 ± 6.1 (mean ± standard deviation, p = 0.49) on 3.2 ± 1.1 and 3.1 ± 1.0 medications (p = 0.53) compared to 11.8 ± 5.2 and 12.8 ± 3.7 (p = 0.36) on 0.5 ± 0.8 and 0.6 ± 1.0 medications (p = 0.63) at 2 years in the MMC and CM groups, respectively. Kaplan-Meier analysis demonstrated complete success rates were similar in both groups at 24 months: 38.4 ± 7.6% with MMC and 56.2 ± 7.9% with CM (mean ± standard error, p = 0.112, log rank test); however, a significantly higher incidence of failure due to persistent hypotony was observed with MMC (p = 0.002). Conclusions Use of the CM implant at the time of trabeculectomy or combined phacoemulsification and trabeculectomy is associated with similar complete success rates compared to adjunctive MMC; however, the risk of persistent hypotony is higher with MMC. Trial registration ClinicalTrials.gov registration numberNCT01440751 . Registered 9/14/11